2019
DOI: 10.2351/1.5046470
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of laser cleaning induced oxidation and corrosion property changes in AA5083 aluminum alloy

Abstract: Laser cleaning of metallic alloys for the purpose of removal of metal oxide layers is based on laser thermal ablation. In laser thermal ablation, the interaction between the laser beam and oxide layer may generate significant thermal effects to induce additional thermal oxidation or even melting a thin layer of the underlying surface. The change of surface oxide status may subsequently affect corrosion behavior of the metallic alloys. In this work, the effects of laser cleaning on corrosion behavior of hot-rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…9.9%), and C (wt. 5.3%), where O content was from the oxidation of metal [ 27 ]. After laser processing, obvious changes in chemical composition of Fe and C were observed.…”
Section: Resultsmentioning
confidence: 99%
“…9.9%), and C (wt. 5.3%), where O content was from the oxidation of metal [ 27 ]. After laser processing, obvious changes in chemical composition of Fe and C were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The change in the laser energy density significantly impacted the removal effect of the oxide films and paint layers from aluminum alloy surfaces. Many studies have shown that the removal effect of oxide film on the aluminum alloy surface initially rises and then falls with increased energy density [ 13 , 33 , 55 , 56 , 57 , 58 , 59 ]. The energy-dispersive X-ray spectroscopy and the X-ray photoelectron spectroscopy (XPS) were used to detect the surface composition of the aluminum alloy.…”
Section: Optimization Of Laser Process Parametersmentioning
confidence: 99%
“…In most of the cases, the laser cleaning would induce the increase of surface roughness (Dong et al, 2017). The laser power, pulse frequency, cleaning speed and other parameters changed surface roughness through the way of changing energy density and overlap ratio (Zhang et al, 2019a(Zhang et al, , 2019b. When the pulse width is wide, the aluminum alloy substrate may be ablated.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported by Dong et al (2017) that using laser at 100 ns pulse width to remove the oxide film of 7A52 aluminum alloy, it was found that the laser ablated the aluminum alloy substrate, formed corrugated grooves and increased the surface roughness. Although three mechanisms have been reported so far in the laser removal of oxide layers from metallic alloys, including thermal ablation, mechanical effect and combined thermal ablation and mechanical effects, the removal of oxide layers on aluminum alloys was dominated by thermal ablation, and the associated thermal effects (Zhang et al, 2019a(Zhang et al, , 2019b. The thermal ablation and associated thermal of the aluminum alloy surface make it easy to reoxidize and form a new oxide film on the substrate.…”
Section: Introductionmentioning
confidence: 99%